GnRH-(1–5) Inhibits TGF-β Signaling to Regulate the Migration of Immortalized Gonadotropin-Releasing Hormone Neurons - Larco, Darwin O.; Bauman, Bradly M.; Cho-Clark, Madelaine; Mani, Shaila K.; Wu, T. John (Frontiers in Endocrinology, 2018)
Gonadotropin-Releasing Hormone (GnRH) neurons originate outside the central nervous system (CNS) in the nasal placode where their migration to the basal forebrain is dependent on the integration of multiple signaling cues during development. The proper migration and establishment of the GnRH neuronal population within the CNS is critical for normal pubertal onset and reproductive function. The endopeptidase EP24.15 is expressed along the migratory path of GnRH neurons and cleaves the full-length GnRH to generate the metabolite GnRH-(1-5). Using the GN11 cell model, which is considered a pre-migratory GnRH neuronal cell line, we demonstrated that GnRH-(1-5) inhibits cellular migration in a wound closure assay by binding the orphan G protein-coupled receptor 173 (GPR173). In our current experiments, we sought to utilize an in vitro migration assay that better reflects the external environment that migrating GnRH neurons are exposed to during development. Therefore, we used a transwell assay where the inserts where coated with or without a matrigel, a gelatinous mixture containing extracellular matrix proteins, to mimic the extracellular environment. Interestingly, GnRH-(1-5) inhibited the ability of GN11 cells to migrate only through extracellular matrix mimetic and was dependent on GPR173. Furthermore, we found that GN11 cells secrete TGF-β1, 2, and 3 but only TGF-β1 release and signaling was inhibited by GnRH-(1-5). To identify potential mechanisms involved in the proteolytic activation of TGF-β, we measured a panel of genes implicated in extracellular matrix remodeling. We found that GnRH-(1-5) consistently increased TIMP1 expression, which is an inhibitor of proteinase activity, leading to a decrease in bioactive TGF-β and subsequent signaling. These results suggest that GnRH-(1-5) activating GPR173 may modulate the response of migrating GnRH neurons to external cues present in the extracellular matrix environment via an autocrine-dependent mechanism involving TGF-β.